The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jbio.201700113
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing biochemical and morphological variations of clinically relevant anatomical locations of oral tissue in vivo with hybrid Raman spectroscopy and optical coherence tomography technique

Abstract: This study aims to characterize biochemical and morphological variations of the clinically relevant anatomical locations of in vivo oral tissue (ie, alveolar process, lateral tongue and floor of the mouth) by using hybrid Raman spectroscopy (RS) and optical coherence tomography (OCT) technique. A total of 1049 in vivo fingerprint (FP: 800-1800 cm ) and high wavenumber (HW: 2800-3600 cm ) Raman spectra were acquired from different oral tissue (alveolar process = 331, lateral tongue = 339 and floor of mouth = 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Another optical technique of interest is the Fourier transformed infrared (FTIR) spectroscopy, which may provide qualitative information about the chemical composition of tissues in a non-invasive way at a molecular level, allowing the analysis of structural and chemical changes caused by pathologies, like neoplasia and osteoporosis, aging, and radiation [22]. This optical technique was also successfully used to detect the changes promoted by laser irradiation in hard tissues and to monitor caries and erosion lesions [11,14,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Another optical technique of interest is the Fourier transformed infrared (FTIR) spectroscopy, which may provide qualitative information about the chemical composition of tissues in a non-invasive way at a molecular level, allowing the analysis of structural and chemical changes caused by pathologies, like neoplasia and osteoporosis, aging, and radiation [22]. This optical technique was also successfully used to detect the changes promoted by laser irradiation in hard tissues and to monitor caries and erosion lesions [11,14,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall probe size of 10.2 × 12.7 × 20.3 cm makes it mainly suitable for skin applications. A side-view hybrid probe for in-vivo real-time measurements was developed, 102,103 making use of the complementary information provided by OCT and Raman spectroscopy. The handheld OCT/RS probe has a length of ∌120 mm with a probe head size of ∌13 mm × 8 mm, making it suitable for in-vivo tissue measurements on human organs, such as the oral cavity, cervix, and skin, or for intraoperative monitoring, e.g., brain surgeries.…”
Section: Multimodal Probesmentioning
confidence: 99%
“…101 In Ref. 103, it was demonstrated that the diagnostic strength of the combination is improved in comparison with Raman spectroscopy or OCT alone. To address the issue of obtaining both morphological and molecular information at depth, a hybrid approach integrating OCT with wavelength modulated spatially offset Raman spectroscopy (WM-SORS) was introduced.…”
Section: Multimodal Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, different biomarkers have been identified for monitoring retinal inflammation, 15 and retinal changes occurring in glaucoma were investigated. 16 The combination of morphologically sensitive methods, such as OCT with Raman spectroscopy has been successfully demonstrated on various biological tissues 17 – 20 and could have profound implications for ophthalmology. Initial combinations of those modalities have readily been performed on ex vivo porcine and human retina tissue.…”
Section: Introductionmentioning
confidence: 99%